1999
DOI: 10.1080/00049539908255340
|View full text |Cite
|
Sign up to set email alerts
|

Experimenter effects on ingroup preference and self-concept of urban aboriginal children

Abstract: The present study investigated the effects of experimenter (Aboriginal &.. Anglo), school culture, gender, and age on 117 Aboriginal-Australian children's ingroup preference and self-concept. Based on self-categorisation theory, an experimenter effect on ingroup preference but not on self-concept, was predicted. Past research led to a further hypothesis that the children would show outgroup preference. Results confirmed that the children showed greater ingroup preference when interviewed by an Aboriginal exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…The presence of an out-group experimenter (e.g., men or Whites) might enhance the relevance of stereotype threat cues given to women or ethnic minorities in testing situations, whereas the presence of an in-group experimenter might create more credibility to a message of stereotype threat-removal. Although the predictive effect of experimenter expectancy bias might be small (e.g., less than 3% of the variance in standardized test results; Janssen, 1973), it is possible that African Americans or women might subconsciously experience discomfort with out-group experimenters according to research on in-group/out-group preference (e.g., Pedersen, Walker, & Glass, 1999). So far little evidence has been gathered to address these specific questions within a stereotype threat paradigm, although a few investigators safeguarded against experimenter effects by using experimenter(s) of the same race/ethnicity or gender as that of stereotype threat targets (e.g., Blascovich, Spencer, Quinn, & Steele, 2001, Study 1; Cadinu et al, 2003; Croizet & Claire, 1998; Nguyen, O'Neal, & Ryan, 2003), using double-blind procedures (e.g., Aronson et al, 1999; Quinn & Spencer, 2001; Shih et al, 1999), or minimizing experimenter presence in test administration (e.g., Inzlicht & Ben-Zeev, 2000, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of an out-group experimenter (e.g., men or Whites) might enhance the relevance of stereotype threat cues given to women or ethnic minorities in testing situations, whereas the presence of an in-group experimenter might create more credibility to a message of stereotype threat-removal. Although the predictive effect of experimenter expectancy bias might be small (e.g., less than 3% of the variance in standardized test results; Janssen, 1973), it is possible that African Americans or women might subconsciously experience discomfort with out-group experimenters according to research on in-group/out-group preference (e.g., Pedersen, Walker, & Glass, 1999). So far little evidence has been gathered to address these specific questions within a stereotype threat paradigm, although a few investigators safeguarded against experimenter effects by using experimenter(s) of the same race/ethnicity or gender as that of stereotype threat targets (e.g., Blascovich, Spencer, Quinn, & Steele, 2001, Study 1; Cadinu et al, 2003; Croizet & Claire, 1998; Nguyen, O'Neal, & Ryan, 2003), using double-blind procedures (e.g., Aronson et al, 1999; Quinn & Spencer, 2001; Shih et al, 1999), or minimizing experimenter presence in test administration (e.g., Inzlicht & Ben-Zeev, 2000, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Participants might have responded differently had the experimenter been of Ethiopian origin, or had they completed the questionnaires at home. Pedersen, Walker, and Glass (1999) showed that indigenous Australian children responded differently on several dimensions to an indigenous and to an Anglo experimenter. These issues, which may challenge the validity of studies involving experimenters and subjects from different cultural backgrounds (as is the case in most studies), exceed the confines of this article.…”
Section: Discussionmentioning
confidence: 99%
“…Projections can be positive and negative (Hamachek, 1974;Nicoll, 1987;Lenney, 1999). For this paper, I will be concentrating on negative projections that promote exclusion where the social other is constantly under observation and constructed as unsafe, and or part of the out-group (Chryssochoou, 2000;Pedersen & Walker, 2000).…”
Section: Projections Of Differencementioning
confidence: 99%